The Impact of STEM-based laboratory activities on pre-service science teachers’ competence perceptions in 21st-Century Skills and STEM Awareness - Ozlem Oktay; Gülşen Koçak; Sabriye Seven (Universitas Pendidikan Indonesia, 2023)
This study aims to investigate the impact of laboratory activities prepared based on STEM-based learning on the competence perceptions in 21st-century skills (learning and innovation skills, life and career, information, media, and technology skills) and STEM awareness. The sample group consisted of 53 pre-service science teachers studying in year 2 of a public university. A quasi-experimental design formed the basis of this experimental study conducted as a quantitative research model. Pre-service teachers were randomly assigned, one to the experimental group (n=28) and the other to the control group (n=25). The experimental group was presented with laboratory activities based on STEM-based learning. In contrast, the control group had only laboratory activities (i.e., a group of students who did not conduct STEM-based laboratory activities). The measurement tools were the 21st Century Skills Competence Perception Scale (21st Century SCS) and the STEM Awareness Scale (SAS). All participants in the study expressed their agreement generally on the level of “I agree” for all three dimensions of the 21st Century SCS regarding STEM. As a result of the implementation, the SCS sub-dimension of “information, media and technology skills” and SAS skills of the experimental group students were higher than those of the students in the control group. It was found that the experimental group used the media and technology effectively and to use technology to access, analyze and share information. It was also thought that the individuals' problem-solving, critical, and high-level thinking skills developed more than the control group, thanks to the higher STEM awareness in the experimental group. Finally, some implications were proposed based on the research results from the STEM-based learning laboratory activities.